UNLOCKING THE POTENTIAL: BUSINESS SYNERGY, AI, AND SOLAR CELL RADIO WAVES FOR SUSTAINABLE ENERGY SOLUTIONS - Bimalendu Pendy (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
This paper explores the convergence of cutting-edge technologies and innovative business strategies to pave the way for sustainable energy solutions. As the global community grapples with the urgent need to address climate change and reduce reliance on fossil fuels, this research delves into the synergistic possibilities of artificial intelligence (AI) and solar cell radio waves to revolutionize the energy landscape. We begin by examining the current challenges and limitations of traditional solar cell technology, including intermittent energy production and high installation costs. Next, we delve into the capabilities of AI, particularly machine learning algorithms, in optimizing energy production, storage, and distribution. By harnessing AI-driven predictive analytics, we can significantly enhance the efficiency and reliability of solar energy systems. We explore the innovative concept of utilizing radio waves generated by solar cells to transmit power wirelessly. This groundbreaking technology not only eliminates the need for costly infrastructure but also offers the potential to transmit energy over long distances, opening up new possibilities for remote and off-grid communities. Additionally, we investigate the business implications of these technological advancements. We discuss the emergence of new business models, collaborations, and investment opportunities in the sustainable energy sector, emphasizing the role of AI in facilitating these transitions. The paper highlights case studies and real-world examples of companies that have successfully integrated AI and solar cell radio waves into their operations, showcasing the tangible benefits and potential profitability of these endeavors. This paper presents a comprehensive overview of the transformative potential of AI and solar cell radio waves in revolutionizing sustainable energy solutions. By harnessing these synergies and embracing innovative business strategies, we can accelerate the transition towards a cleaner, more sustainable energy future, mitigating the adverse effects of climate change and ensuring a brighter tomorrow for all.